2002
DOI: 10.1002/er.786
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance analysis of a tube finned surface

Abstract: SUMMARYThe present work submits an experimental work on the heat transfer and friction loss characteristic, employing a tube "nned heating surface kept at a constant temperature in a rectangular channel. The tube "ns attached on the surface (o.d."29 mm) were arranged as either in-line or staggered. The parameters for the study were Reynolds number (3700}30 000), depending on hydraulic diameter, the distance between the tube "ns in the #ow direction (S W /D"1.72}3.45) and the "n arrangement. The change in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…While there are many factors that influence patient's satisfaction including characteristics of the patient and properties of health-care provides, interpersonal relationships between medical staff and with patients was the strongest factor (Batbaatar et al, 2017;Graham et al, 2015;Songthamwat et al, 2017). Qarari, Anwar, Basri, and Nuraeni (2018) revealed that understanding of patient's needs, schedule of patient visits, two-way communication, speed of response, and easiness of contact are basic factors of patient satisfaction in hospitals. However, interaction with doctor influences the quality of the service and the patient's outcome (Tsai, Orav, & Jha, 2015;Sacks et al, 2015;Chen et al, 2018).…”
Section: Patient Satisfaction In the Healthcare Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are many factors that influence patient's satisfaction including characteristics of the patient and properties of health-care provides, interpersonal relationships between medical staff and with patients was the strongest factor (Batbaatar et al, 2017;Graham et al, 2015;Songthamwat et al, 2017). Qarari, Anwar, Basri, and Nuraeni (2018) revealed that understanding of patient's needs, schedule of patient visits, two-way communication, speed of response, and easiness of contact are basic factors of patient satisfaction in hospitals. However, interaction with doctor influences the quality of the service and the patient's outcome (Tsai, Orav, & Jha, 2015;Sacks et al, 2015;Chen et al, 2018).…”
Section: Patient Satisfaction In the Healthcare Settingmentioning
confidence: 99%
“…In addition to the properties of communication, setting impacts patient experience at the hospital. Hospitality, availability of equipment, and responsiveness to complain are directly related to the client's satisfaction (Qarari et al, 2018;Mohammed et al, 2016;Menendez et al, 2019). A welcoming atmosphere, pleasant interpersonal communication, and personnel training are related to customer's satisfaction and sense of self-worth among customers (Leonard, 2017;Boissy et al, 2016).…”
Section: Patient Satisfaction In the Healthcare Settingmentioning
confidence: 99%
“…Swirl flow devices based on passive method have been developed and are most widely applied to concentric pipe heat exchangers as heat transfer enhancement technologies . In this case, there has been effective improvement of heat exchangers based on extensive research via experimental and numerical investigation on heat transfer performance and pressure drop characteristics of swirl flow applications .…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of system performance as part of the planning and design of a power plant improves both static and dynamic operating phase system behavior. Most previous investigations of exhaust gas flow across tube banks were performed considering a homogeneous equilibrium model for a two-phase flow on the tube side [7][8][9]. The homogeneous equilibrium model assumes that the steam and water phases are flowing at the same velocity.…”
Section: Introductionmentioning
confidence: 99%